Engineering CD5-targeting CAR-NK cells from peripheral blood for the treatment of CD5-positive hematological malignancies - Haolong Lin; Lingfeng Zhang; Tong Ge; Ning An; Yongkun Yang; Yicheng Zhang; Wei Mu (Journal of Translational Medicine)
Abstract Background The therapeutic application of chimeric antigen receptor (CAR) T cells in T-cell malignancies faces substantial limitations owing to fratricide and potential T cell aplasia, primarily attributed to the shared expression of target antigens, such as CD5, between normal and malignant T cells. Although natural killer (NK) cell-based immunotherapy is a promising alternative approach, its efficacy in treating hematologic malignancies remains to be fully elucidated. Methods CD5-targeted CAR-modified primary NK cells, T cells and NK92 cell lines were generated and comprehensively evaluated for their anti-tumor efficacy through in vitro cytotoxicity assays and xenograft mouse models. Furthermore, preliminary investigation of the herpes simplex virus-1 thymidine kinase (HSV-TK) suicide switch system in CAR-NK cells were conducted using ganciclovir (GCV) as the activating agent. Results CAR-NK cells exhibited significantly increased cytotoxic activity against CD5-positive cell lines and primary tumor cells, compared to NK, CAR-NK92, and CAR-T cells. Moreover, CAR-NK cells effectively decreased the leukemic burden and extended survival in murine model. Additionally, an off-switch utilizing the HSV-TK switch system successfully eradicated CAR-NK cells for safety considerations. Conclusions This study developed a controllable CD5 CAR-NK cells that exhibit high efficacy against T-cell malignancies, although further validation is necessary to assess their clinical potential.